The influence of psychological factors on the frequency and perception of post-endodontic pain - Mijailovic, Marija; Kolak, Veljko (Vojnosanitetski pregled, 2024)
Background/Aim. Post-endodontic pain (PEP) is associated with the presence of any uncomfortable feeling or sensitivity that occurs within a few hours or a few days after the endodontic treatment. The aim of this study was to evaluate the possible association between psychological factors and the frequency and perception of PEP. Methods. The study sample consisted of 140 patients with incisors, canines, or premolars indicated for root canal treatment (RCT) without periapical pathology. A single experienced endodontist was involved in the procedure, and the same clinical protocol was used for all the patients. Participants psychometric evaluation was done using the Depression Anxiety Stress Scale 21 (DASS-21). PEP levels were assessed using a Visual Analog Scale at different intervals (24, 48, and 72-hour intervals and after a week). Results. The presence of postoperative pain was reported in 63.6% of the respondents. The vast majority rated the pain intensity as mild, and the pain significantly decreased over evaluated time intervals. Participants who exhibited higher scores for depression, anxiety, and stress reported significantly higher pain intensity. The multivariate logistic regression analysis showed that tooth type (p = 0.001) and high anxiety score (p = 0.035) were directly associated with the occurrence of pain after therapy.  Conclusion. Psychological factors, such as depression, stress, and anxiety, influenced pain perception after RCT treatment, and a high anxiety score was directly associated with the frequency of post-obturation pain.
Keywords: anxiety; depression; pain, postoperative; psychology; root canal therapy; stress, psychological; surveys and questionnaires.